The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0885328219889630
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of aspirin improves osseointegration of hydroxyapatite-coated titanium implants in ovariectomized rats through activation of the Notch signaling pathway

Abstract: Osteoporosis-induced impaired bone regeneration would result in compromised osseointegration of hydroxyapatite-coated titanium and high rate of implant failure. Local administration of aspirin promotes osteoblast proliferation and inhibits osteoclast proliferation, and positively affects bone regeneration in osteoporotic condition. We hypothesized that reduced osteogenesis may account for poor osseointegration of hydroxyapatite-coated titanium which could be ameliorated by using local aspirin. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Recently, Tao et al (2020) suggested that local incorporation of Acetylsalicylic Acid into HAp-coated Ti implants is useful to improve osseointegration by increasing bone formation around the implant through the activation of Notch signaling pathways, both in the osteoporotic and normal condition [ 31 ]. In addition, current animal studies demonstrate a possible improvement of osseointegration of the orthopedic implant in animal models from both systemic and local administration of Zoledronate [ 32 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Recently, Tao et al (2020) suggested that local incorporation of Acetylsalicylic Acid into HAp-coated Ti implants is useful to improve osseointegration by increasing bone formation around the implant through the activation of Notch signaling pathways, both in the osteoporotic and normal condition [ 31 ]. In addition, current animal studies demonstrate a possible improvement of osseointegration of the orthopedic implant in animal models from both systemic and local administration of Zoledronate [ 32 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…The rats were allowed for 12 weeks to conduct an osteoporosis as previous reports described. 22,23 The femurs of each five randomly selected OVX rats and the five shamoperated ones were harvested for bone mineral density (BMD) evaluation by micro computed tomography (Micro-CT) and hematoxylin(HE) staining to confirm the establishment of osteoporosis. Afterwards, all animals were randomly divided into three experimental groups: Sham group, OVX group and TUDCA group, the rats from OVX and Sham received HA implants and animals belonging to group TUDCA received TUDCA-HA implants as previously described.…”
Section: Surgery and Treatmentmentioning
confidence: 99%
“…The specimens were cut into 200-mm thick sections using a microtome(Leica Microsystems Ltd, Wetzlar, Germany) and were subsequently ground and polished to a thickness of 40-50 mm as previously described. 22,23 The femur specimens were stained in Von-Gieson for histopathological examination.…”
Section: Histological Examinationmentioning
confidence: 99%
“…Following Micro-CT scanning, the femur specimens were dehydrated by alcohols and embedded in PMMA. The specimens were cut into 200-μm thick sections using a microtome(Leica Microsystems Ltd, Wetzlar, Germany) and were subsequently ground and polished to a thickness of 40-50 μm as previously described [21,22]. The femur specimens were stained in Von-Gieson for histopathological examination.…”
Section: Histological Examinationmentioning
confidence: 99%
“…Total RNA was prepared and isolated using Trizol reagent (Invitrogen Corp., Carlsbad, CA, USA) as previously described [24,22]. Brie y, tissue samples around implant were homogenized using a mortar and pestle with liquid nitrogen, using 5ml of TRIzol per 50-100 mg of tissue.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reaction(rt-qpcr) Analysismentioning
confidence: 99%